2014
DOI: 10.1002/aenm.201401745
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Doping Methods for Radial p/n Junctions in Silicon

Abstract: P/n and n/p junctions with depths of 200 nm to several micrometers have been created in flat silicon substrates as well as on 3D microstructures by means of a variety of methods, including solid source dotation (SSD), low‐pressure chemical vapor deposition (LPCVD), atmospheric pressure chemical vapor deposition, and plasma‐enhanced chemical vapor deposition. Radial junctions in Si micropillars are inspected by optical and scanning electron micro­scopies, using a CrO3‐based staining solution, which enables visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(60 citation statements)
references
References 28 publications
1
59
0
Order By: Relevance
“…[ 7 ] Junction depths were experimentally verifi ed by ball grooving and staining experiments on fi ve different fl at samples (140, 790, 900, 1170, and 1550 nm). Since the phosphorus surface concentration upon drive-in is relatively low, transport of phosphorus into silicon can be described by Fick's law of diffusion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 7 ] Junction depths were experimentally verifi ed by ball grooving and staining experiments on fi ve different fl at samples (140, 790, 900, 1170, and 1550 nm). Since the phosphorus surface concentration upon drive-in is relatively low, transport of phosphorus into silicon can be described by Fick's law of diffusion.…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] In summary, p-type silicon {100} substrates (5-10 Ω cm, 525 µm thickness, single side polished, Cz-grown, Okmetic Finland) were covered with 100 nm silicon nitride (SiN x ). On the front side, after removal of SiN x , the substrate was patterned with arrays of hexagonally packed dots (4 µm diameter, 6 µm pitch, 0.5 × 0.5 cm 2 cell size on a specimen of 2 cm × 2 cm) by standard photolithography (Olin 907-17 photoresist).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chakthranont et al used so-called black silicon which shows a very high light absorption and is composed of needle-shaped (tapered) nanowires, in their case ~3 μm length, ~200 nm average diameter and ~300 nm spacing. We assume that the microwires in our system do absorb more light than flat equivalents as proven by Elbersen et al [46,47] and Kelzenberg et al [25] but believe that mass transfer overcompensates this effect and leads to an overall underperformance of the microwire structures compared to flat samples. In contrast, the positive light trapping effect of microwires overcompensated the negative diffusion effect in the system reported by Chakthranont et al as these authors used smaller microwire dimensions leading to a significantly shorter ion diffusion path length.…”
Section: Light Absorption Propertiesmentioning
confidence: 99%
“…[25,46] For instance, Elbersen et al have studied the effects of microwire length on photovoltaic activity of silicon microwires with radial p/n junctions and a spacing of 2 µm and found that all tested microwires with a length between 10 µm and 60 µm outperformed flat equivalents under perpendicularly oriented illumination. [47] However, Boettcher et al prepared similarly sized microwire arrays with a radial n + /p junction, deposited platinum on the tops and tested them for photocatalytic hydrogen evolution.…”
Section: Light Absorption Propertiesmentioning
confidence: 99%